Bioacoustic Analysis for Help Identify Andestimate Distribution of Anura Due to the Effects of Ecotourism in the CA-TWA Region of Telaga Warna - tri wahyuningsih; Rusna Ristasa A.; Maman Rumanta; Anna Ratnaningsih (Jurnal Penelitian Pendidikan IPA, 2023)
Indonesia is a country with very high biodiversity and is known as Mega Biodiversity. In Indonesia found about 450 species of Anura representing about 11% of all species in the world, and 28 species ofwhich 28 live in West Java.  Anura animals have a pattern of calling behavior that is essential for mating: males produce call-up behavior that attracts females and, in some species, represents the extent of their territory. Research on frogs and toads is considered necessary considering the absence of more detailed data on the bioacoustics of these frogs, especially in the West Java area, so that variations and patterns of anura sounds are known in the Telaga Warna Nature Reserve and Nature Park (CA-TWA) area and can make scientific contributions in information on variations and sound patterns owned by anura animals in terms of anura conservation in Indonesia.  This research was conducted from month March-December 2018, located in Telaga Warna Nature Reserve and Nature Park, Bogor, West Java.  Call the recording every 6:00 p.m. to 11:00 p.m. each night during the sampling period.  The number of anura species in the villa and swamp areas is more abundant than the lake area, and the presence of Pearl maroon frogs (nyctixalus margaritifer) found in the villa and lake areas, while the Bufo melanotictus type that likes to live in the lake area. It can be seen that the villa and swamp areas are still maintained vegetation by looking at the medium density of the canopy. Steeper slope conditions help the flow of nutrients from the soil due to the erosion process and settle in flat to gentle areas. The density of the canopy in the area helps maintain the surface temperature of the land with a stable land surface temperature ranging from 15 – 21 0C.